(untitled) (International Journal of Technology and Management Research, 2020)
The study was undertaken to assess how companies use the activity of budgeting and budgetary control in their management process to achieve their desired results. Logs & Lumber Limited, a timber company in Kumasi, Ghana was studied. Convenient sampling method was used to select the respondents.. The sample was made up of 17 staff members of the company. The primary data were gathered through questionnaires and structured interview. The secondary data were budget reports and budget manual of the company from 2011-2015. The data obtained from the study were processed using the Stastical Package Software System (SPSS) version 16.0 to assess differences in the results. 100% of the respondents strongly agree that the company budget practices do not contradict with literature. It is concluded that to ensure an effective an efficient budget and budgetary control system identifying and mitigating limiting factors to budgets are the most relevant. Keywords: Budgeting, budgetary control, timber industry, logs and lumber limited